Absence of Bsep/Abcb11 attenuates MCD diet‐induced hepatic steatosis but aggravates inflammation in mice. (18th March 2020) - Fuchs, Claudia D.; Krivanec, Sebastian; Steinacher, Daniel; Mlitz, Veronika; Wahlström, Annika; Stahlman, Marcus; Claudel, Thierry; Scharnagl, Hubert; Stojakovic, Tatjana; Marschall, Hanns‐Ulrich; Trauner, Michael
Abstract: Background: Bile acids (BAs) regulate hepatic lipid metabolism and inflammation. Bile salt export pump (BSEP) KO mice are metabolically preconditioned with a hydrophilic BA composition protecting them from cholestasis. We hypothesize that changes in hepatic BA profile and subsequent changes in BA signalling may critically determine the susceptibility to steatohepatitis. Methods: Wild‐type (WT) and BSEP KO mice were challenged with methionine choline‐deficient (MCD) diet to induce steatohepatitis. Serum biochemistry, lipid profiling as well as intestinal lipid absorption were assessed. Markers of inflammation, fibrosis, lipid and BA metabolism were analysed. Hepatic and faecal BA profile as well as serum levels of the BA synthesis intermediate 7‐hydroxy‐4‐cholesten‐3‐one (C4) were also investigated. Results: Bile salt export pump KO MCD‐fed mice developed less steatosis but more inflammation than WT mice. Intestinal neutral lipid levels were reduced in BSEP KO mice at baseline and under MCD conditions. Faecal non‐esterified fatty acid concentrations at baseline and under MCD diet were markedly elevated in BSEP KO compared to WT mice. Serum liver enzymes and hepatic expression of inflammatory markers were increased in MCD‐fed BSEP KO animals. PPARα protein levels were reduced in BSEP KO mice. Accordingly, PPARα downstream targets Fabp1 and Fatp5 were repressed, while NFκB subunits were increased in MCD‐fed BSEP KO mice. Farnesoid X receptor (FXR) protein levels were reduced in MCD‐fed BSEP KO vs WT mice. Hepatic BA profile revealed elevated levels of TβMCA, exerting FXR antagonistic action, while concentrations of TCA (FXR agonistic function) were reduced. Conclusion: Presence of hydroxylated BAs result in increased faecal FA excretion and reduced hepatic lipid accumulation. This aggravates development of MCD diet‐induced hepatitis potentially by decreasing FXR and PPARα signalling.